2009
DOI: 10.1128/mcb.01035-08
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RNA-Binding Protein, Ossa/C9orf10, Regulates Activity of Src Kinases To Protect Cells from Oxidative Stress-Induced Apoptosis

Abstract: During the process of tumor progression and clinical treatments, tumor cells are exposed to oxidative stress. Tumor cells are frequently resistant to such stress by producing antiapoptotic signaling, including activation of Src family kinases (SFKs), although the molecular mechanism is not clear. In an attempt to identify the SFK-binding proteins selectively phosphorylated in gastric scirrhous carcinoma, we identified an uncharacterized protein, C9orf10. Here we report that C9orf10 (designated Ossa for oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 40 publications
7
54
0
Order By: Relevance
“…In this report, we describe a key role for FAM120A, also known as OSSA or C9orf10 (16), in the signal transduction of IL13 through IL13Ra2 for the migration and invasion of colon cancer cells. FAM120A was identified as a scaffold protein that interacts with IL13Ra2 using mass spectrometry and coimmunoprecipitation experiments.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this report, we describe a key role for FAM120A, also known as OSSA or C9orf10 (16), in the signal transduction of IL13 through IL13Ra2 for the migration and invasion of colon cancer cells. FAM120A was identified as a scaffold protein that interacts with IL13Ra2 using mass spectrometry and coimmunoprecipitation experiments.…”
Section: Discussionmentioning
confidence: 98%
“…FAM120A recruits PI3K and works as a scaffold protein for PI3K and the Src family kinases (SFK), enabling phosphorylation and activation of PI3K (16). Silencing of FAM120A impaired the activation of PI3K, AKT, and mTOR in the metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the 58As9 and NKPS cell lines are highly metastatic (Yanagihara et al, 2005;Tanaka et al, 2009). After establishing 58As9 and NKPS cells that stably expressed wild-type ARAP3, we injected the cells into the peritoneal cavities of BALB/c nude mice (Figure 3 and Supplemental Figure 1).…”
Section: Roles Of Arap3 In Peritoneal Disseminationmentioning
confidence: 99%
“…Recently, we reported that Src substrates such as CUB domain-containing protein 1 (CDCP1) (Uekita et al, 2008) and Homo sapiens chromosome 9 open reading frame 10/oxidative stress-associated Src activator (C9orf10/Ossa) (Tanaka et al, 2009) are hyperphosphorylated in the peritoneal nodules formed after inoculating the scirrhous gastric carcinoma cell line 44As3 into BALB/c nude mice. In our studies, we also detected another substrate of Src, Arf-GAP with Rho-GTPase-activated protein (GAP) domain, ankyrin repeat and PH domain 3 (ARAP3), in these nodules.…”
Section: Introductionmentioning
confidence: 99%